Pitting corrosion-resistant martensitic stainless steel and method for producing the same
Patent Information
- Application Number
- JP2023555430
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-03-09
- Filing Date
- 2022-03-03
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2042-03-03
Smart Images

Figure 0007943861000001
Abstract
Description
TECHNICAL FIELD
[0001] The invention disclosed in the present application generally relates to corrosion-resistant stainless steels. In particular, the invention relates to pitting corrosion-resistant martensitic stainless steels, including those suitable for rotating components of turbines. BACKGROUND ART
[0002] Metal alloys used for rotating components of gas turbines, particularly for front-stage compressor airfoils including moving blades and stationary vanes, must possess a combination of high strength, toughness, fatigue resistance and other physical and mechanical properties to provide these machines with required operating characteristics. Furthermore, the alloys used must have sufficient resistance to various forms of corrosion and corrosion mechanisms, particularly pitting corrosion, due to the extreme operating environment of turbines, including exposure to various ionic reactive species such as various chemical species including chlorides, sulfates, nitrides and other corrosive species. Corrosion may degrade other required physical and mechanical properties such as high-cycle fatigue strength through the initiation of surface cracks that propagate under the cyclic heat and stress associated with turbine operation.
[0003] Currently, no high-tensile steel possesses sufficient pitting corrosion resistance to withstand harsh marine / industrial environments such as coastal industrial power plants for two to three years or more. Even alloys known to have numerous advantageous corrosion resistance properties, including resistance to intergranular attack, such as 450 and 450+ stainless steels, remain susceptible to pitting corrosion mechanisms. While these martensitic stainless steels have provided a combination of corrosion resistance, mechanical strength, and fracture toughness suitable for use in steam and gas turbine rotating components, these alloys are still known to be prone to pitting corrosion. For example, stainless steel airfoils used in the front-end compressors of industrial gas turbines have been found to be susceptible to pitting corrosion on the surface of the airfoil, particularly on the leading edge. Although not theoretically bound, pitting corrosion is thought to be related to various electrochemical reaction processes activated by airborne deposits on the airfoil surface, especially corrosive chemical species present in the deposits and moisture from the intake air. Electrochemically induced pitting corrosion on the airfoil surface can lead to cracking of the airfoil due to the periodic heat and operating stresses experienced by these components. High levels of moisture can arise from various sources, including use in high-moisture environments such as facilities near the sea or other bodies of water, and from online water washing, fogging, evaporative cooling, or various combinations thereof, to improve compressor efficiency. Since turbines are often installed in highly corrosive environments, such as near chemical and petrochemical plants where various chemical species may be present in the intake air, coastlines and other saline environments where various sea salts may be present in the intake air, or combinations thereof, or in other applications where corrosive chemical species are present in the inlet air, corrosive contaminants are commonly generated in the turbine operating environment.
[0004] From the above perspective, it would be highly desirable to have a stainless steel alloy that is suitable for use as a turbine blade, particularly as an industrial gas turbine blade, in the aforementioned operating environment, and that also has improved pitting corrosion resistance. [Prior art documents] [Patent Documents]
[0005] [Patent Document 1] U.S. Patent Application Publication No. 2009 / 081068 [Overview of the Initiative]
[0006] In one embodiment, a method for manufacturing a forged martensitic stainless steel alloy is provided. The method includes a step of preparing a forged preform of a martensitic pitting-resistant stainless steel alloy containing about 12.0% to about 16.0% by weight of chromium, more than 16.0% to about 20.0% by weight of cobalt, about 6.0% to about 8.0% by weight of molybdenum, about 1.0% to about 3.0% by weight of nickel, about 0.020% to about 0.040% by weight of carbon, the remainder being iron and unavoidable impurities. The alloy has a microstructure containing less than 2 volume percent or 2% or less of retained austenite phase in its microstructure. In a heating step, the forged preform is heated to a solution temperature for a time sufficient to form a solution microstructure. In the cooling step, the forged preform and solution-treated microstructure are cooled to room temperature in a liquid. Then, in the immersion step, the forged preform is immersed in a cryogenic liquid to transform the retained austenite phase in the microstructure into martensite. In the heating step, the forged preform is heated to a tempering temperature of less than 600°F for a tempering time sufficient to form a tempered forged preform containing a tempered martensite microstructure. In the cooling step, the tempered forged preform is cooled to room temperature.
[0007] In another embodiment, a method for manufacturing a forged martensitic stainless steel alloy is provided. The method includes a step of preparing a forged preform of a martensitic pitting-resistant stainless steel alloy containing about 12.0% to about 16.0% by weight of chromium, more than 16.0% to about 20.0% by weight of cobalt, about 6.0% to about 8.0% by weight of molybdenum, about 1.0% to about 3.0% by weight of nickel, about 0.020% to about 0.040% by weight of carbon, the remainder being iron and unavoidable impurities. The alloy has a microstructure in which retained austenite phase is contained in less than 2% by volume of the microstructure. In a heating step, the forged preform is heated to a solution temperature for a time sufficient to form a solution microstructure. In a cooling step, the forged preform and the solution microstructure are cooled to room temperature with a liquid, the liquid being oil. The forged preform is immersed in oil, and then, in a immersion step, the forged preform is immersed in a cryogenic liquid to transform the retained austenite phase in the microstructure into martensite. The cryogenic liquid is liquid nitrogen or liquid helium at a temperature below -300°F. In a second heating step, the forged preform is heated to a tempering temperature below 600°F for a tempering time sufficient to form a tempered forged preform containing a tempered martensite microstructure. In a second cooling step, the tempered forged preform is cooled to room temperature.
[0008] In yet another embodiment, the forged martensitic stainless steel alloy contains about 12.0% to about 16.0% by weight of chromium, more than 16.0% to about 20.0% by weight of cobalt, about 6.0% to about 8.0% by weight of molybdenum, about 1.0% to about 3.0% by weight of nickel, about 0.020% to about 0.040% by weight of carbon, the remainder being iron and unavoidable impurities. The alloy has a microstructure in which retained austenite phase is present in less than 2 volume percent of the microstructure. The alloy has a microstructure that is substantially free of sigma (σ) phase. The alloy has a microstructure that is substantially free of Laves (Laves) phase, chi (χ) phase and delta (δ) ferrite phase. The alloy may be a turbine blade preform or a compressor blade preform.
[0009] In another embodiment, the forged martensitic stainless steel alloy contains about 12.0% to about 16.0% by weight of chromium, over 16.0% to about 20.0% by weight of cobalt, about 6.0% to about 8.0% by weight of molybdenum, about 1.0% to about 3.0% by weight of nickel, about 0.020% to about 0.040% by weight of carbon, the remainder being iron and unavoidable impurities. The alloy has a microstructure that is substantially free of sigma phases.
[0010] The other advantages and features mentioned above will become clearer when you refer to the following detailed description in conjunction with the attached drawings. [Brief explanation of the drawing]
[0011] The technical aspects considered to be the present invention are identified and clearly stated in the last claim of this specification. Other features and advantages of the embodiments described herein will become apparent from the following detailed description in conjunction with the accompanying drawings. [Figure 1] A flowchart of one embodiment of the method for manufacturing the martensitic stainless steel alloy disclosed in this application.
[0012] In the following detailed description, various embodiments will be explained, along with their advantages and features, with reference to the drawings, for illustrative purposes. [Modes for carrying out the invention]
[0013] The pitting corrosion described above is currently observed in the airfoil sections of forward-stage compressors in service. The pitting-resistant martensitic stainless steel alloys and methods described herein provide corrosion-resistant and pitting-resistant iron-based materials, which represent a significant improvement in terms of service reliability, maintenance concerns and cost reduction, and avoidance of unplanned downtime due to airfoil failures for numerous heavy-duty marine and industrial applications susceptible to the pitting corrosion phenomena described above, including the airfoil sections of forward-stage turbine compressors. The stainless steel alloys described herein have particularly high pitting resistance compared to GTD-450 and GTD-450+ stainless steels. Due to the significant operating costs associated with downtime of industrial gas turbines, including the cost of purchased electricity to replace turbine output, maintenance costs for dismantling the turbine to repair or replace the airfoils, and the cost of repairing or replacing the airfoils themselves, there is considerable commercial value in improving the pitting resistance of alloys and their manufacturing methods. An additional advantage of the pitting-resistant iron-based alloys and their manufacturing methods is that there is no need for additional separate coatings for pitting protection. The stainless steel alloy described in this application is specially constructed and well suitable for forging, particularly for forging turbine blade components.
[0014] In exemplary embodiments, the forged martensitic stainless steel alloy contains about 12.0% to about 16.0% by weight of chromium, more than 16.0% to about 20.0% by weight of cobalt, about 6.0% to about 8.0% by weight of molybdenum, about 1.0% to about 3.0% by weight of nickel, about 0.020% to about 0.040% by weight of carbon, the remainder being iron and unavoidable impurities. More specifically, the forged martensitic stainless steel alloy contains about 13.5% to about 14.5% by weight of chromium, more than 16.0% to about 20.0% by weight of cobalt, about 6.0% to about 6.5% by weight of molybdenum, about 1.0% to about 3.0% by weight of nickel, about 0.020% to about 0.30% by weight of carbon, the remainder being iron and unavoidable impurities. More specifically, the forged martensitic stainless steel alloy contains about 14 wt% chromium, over 16.0 wt% to about 20.0 wt% cobalt, about 6.0 wt% molybdenum, about 1.0 wt% to about 3.0 wt% nickel, about 0.025 wt% carbon, the remainder being iron and unavoidable impurities. The stainless steel alloy composition is selected and constructed to yield a martensitic microstructure by the heat treatment described herein. The stainless steel alloy composition is selected and constructed to yield a martensitic stainless steel alloy having a minimum tensile strength of about 150 ksi, a molybdenum content of over 6%, and a pitting resistance equivalent number (PREN) of over 31.8. The stainless steel alloy disclosed herein achieves these corrosion and strength properties through a combination of compositional chemistry and heat treatment. For example, the stainless steel alloy disclosed herein exhibits excellent resistance to pitting corrosion and can be heat-treated to provide high strength and fracture toughness suitable for applications such as rotor and stator blades for industrial gas turbines and other early-stage turbine compressor airfoil sections (e.g., stages 1 to 5). In another embodiment, the stainless steel alloy described herein obtains strength mainly through the development of a martensitic microstructure and solid solution strengthening associated with martensitic reactions, while simultaneously reducing or minimizing the amount of retained austenite, being substantially free of delta ferrite, and in some embodiments being completely free of delta ferrite.Large amounts of retained austenite (e.g., more than 2%) have been proven to be detrimental to corrosion resistance, and an upper limit of 2% (i.e., less than 2% or 2% or less of retained austenite) is preferred.
[0015] The pitting corrosion index provides guidelines for comparing the pitting corrosion resistance (PREN) of stainless steel alloys based on alloy chemistry. A higher PREN indicates greater resistance to pitting corrosion, but there are practical limits to how high the value can be before the alloy's ability to be properly heat-treated is compromised. PREN can be calculated using Equation 1 below. PREN=(%Cr)+3.3(%Mo)+16(%N) (1) The martensitic stainless steel alloy described in this application has a PREN greater than about 31.8, and particularly greater than about 33.3. In one embodiment, the PREN is greater than about 31.8 to about 42.4, and particularly greater than about 33.3 to about 36.0.
[0016] The stainless steel alloy disclosed herein can be described as an iron-based alloy containing five alloying components, including Cr, Mo, Co, Ni, and C. All other elements are impurities associated with the manufacture of stainless steel and may contain, in weight percent, for example, Mn (≤0.25), Al (≤0.03), V (≤0.10), Si (≤0.25), S (≤0.005), or P (≤0.02), and are kept below the maximum specified levels described herein to ensure consistency of properties and microstructure between lots. When balanced within the above ranges, the disclosed stainless steel alloy yields a martensitic microstructure with desirable strength and fracture toughness levels, along with pitting corrosion resistance.
[0017] As mentioned above, chromium (Cr) is an essential component and is present in an amount sufficient to form a passive film of chromium oxide on the alloy surface. In one embodiment, Cr is present in an amount of about 11.5% by weight or more. In another embodiment, Cr is present in an amount of about 12 to about 16% by weight, more specifically about 13.5 to about 14.5% by weight, and even more specifically about 14% by weight.
[0018] As shown in Equation 1, molybdenum (Mo) has a greater influence than chromium (Cr) on the pitting corrosion resistance of stainless steel. In one embodiment, Mo is present in amounts of approximately 6.0–8.0% by weight, more specifically approximately 6.0–6.5% by weight, and even more specifically approximately 6% by weight. Approximately 6% by weight or more is required to ensure sufficient resistance to pitting corrosion in the chloride environment of the sea. Research has shown that Mo enhances the repassivation ability of stainless steel. Conventional high-Mo content stainless steels are typically either ferritic grades or austenitic grades with high levels of nickel (Ni). The martensitic high-Mo content stainless steel grades discussed here generally focus on utilizing the ultra-high strength properties present in high-temperature tempered materials and are designed and heat-treated at high tempering temperatures, such as 1100°F, for use at high operating temperatures. However, in these materials, at high tempering temperatures, corrosion resistance and toughness are sacrificed because the corrosion-resistant elements Mo and Cr matrix are depleted by the precipitation and formation of Mo-rich and Cr-rich intermetallic compound phases. At high tempering temperatures, a secondary hardening effect also occurs due to the formation of these intermetallic compounds. These intermetallic compound phases include the Raves phase (Fe2Mo), Fe7Mo6, FeMo, the sigma phase (Fe-Cr-Mo), and the complex BCC-kai phase (Fe-Cr-Mo). The sigma phase can form during quenching and tempering and is an undesirable trace component. Cobalt is not involved in the phases associated with these precipitation reactions. These intermetallic compound phases also dramatically reduce the toughness of the alloy. Therefore, the martensitic stainless steel alloys described herein are tempered at low tempering temperatures as described herein to avoid the precipitation of these intermetallic compound phases. Tempered alloys are suitable for use in relatively low-temperature applications where corrosion resistance with moderate strength and good toughness is important. The martensitic stainless steel alloy described in this application maintains a high level of toughness by keeping Mo and Cr in a solid solution, thereby avoiding the formation of intermetallic compound phases by harmonizing the high Mo content with a low tempering temperature region of the hardness-to-tempering temperature curve.In one embodiment, the microstructure of the martensitic stainless steel alloy is substantially free of the Raves phase, and in some embodiments, completely free of the Raves phase. In another embodiment, the microstructure of the martensitic stainless steel alloy is substantially free of the chi phase, and in some embodiments, completely free of the chi phase. In yet another embodiment, the microstructure of the martensitic stainless steel alloy is substantially free of the delta ferrite phase, and in some embodiments, completely free of the delta ferrite phase. In yet another embodiment, the microstructure of the martensitic stainless steel alloy is substantially free of the sigma phase, and in some embodiments, completely free of the sigma phase. In yet another embodiment, the microstructure of the martensitic stainless steel alloy is substantially free of the Raves phase, chi phase, delta ferrite phase, and sigma phase, and in some embodiments, completely free of the Raves phase, chi phase, delta ferrite phase, and sigma phase.
[0019] As can be seen from Equation 1, N has a significant effect on PREN and may be appropriately included in the stainless steel material described in the claims. However, it is difficult to add large amounts of N to the vacuum molten material. Furthermore, N may combine with Cr in the alloy microstructure to form chromium nitrides, which may embrittle and sensitize the stainless steel material due to localized depletion of chromium in the microstructure, especially on the alloy surface that may come into contact with corrosive chemical species. Therefore, when present, N is generally present in amounts of 0.02% by weight or less, and more specifically in amounts of about 0.001 to about 0.02% by weight.
[0020] To develop a martensitic microstructure from martensitic transformation, a high-temperature austenite microstructure is required. Therefore, the composition of the stainless steel alloy described in the claims will have a high-temperature microstructure containing austenite. Since both Cr and Mo are ferrite stabilizers, an austenite-forming agent is required to balance the phase diagram, promote martensite heat treatment to bring about a martensitic microstructure, develop a high-temperature austenite phase, and develop a predetermined maximum amount of retained austenite so as to substantially eliminate delta ferrite. In some embodiments, delta ferrite is completely absent. In this alloy, retained austenite is undesirable and should be kept below 2%. Co was selected to stabilize the austenite. In one embodiment, Co is present in an amount of about 16.0 to about 20.0% by weight, more specifically about 16.5 to about 20.0% by weight, and even more specifically about 16.5 to about 18.0% by weight. As an austenite stabilizer, cobalt provides a sufficiently large austenite phase region for the temperature and / or time tolerance in the heat treatment process. Furthermore, it facilitates martensite initiation (M S The effect of Co on temperature is not as pronounced as that of Ni. Standard quenching and tempering protocols are insufficient for the alloys described herein. To transform the austenite remaining after conventional quenching into martensite, cryogenic treatment with a cryogenic liquid (such as liquid nitrogen or liquid helium) at temperatures below -300°F is required. This cryogenic operation is performed between the quenching and tempering processes.
[0021] Ni is an essential element and is present in an amount sufficient to stabilize austenite. Ni is an austenite stabilizer and increases the amount of retained austenite in these alloys. Therefore, the amount of Ni should be controlled to provide a predetermined maximum amount of retained austenite phase in the alloy microstructure. In one embodiment, the predetermined maximum amount of the retained austenite phase accounts for 2 vol% or less (i.e., 0 to 2 vol%) of the alloy microstructure. In other embodiments, the predetermined amount of the retained austenite phase accounts for about 0 to 1.5 vol%, 0.5 to 2 vol%, or 0.5 to 1.5 vol% of the alloy microstructure. In one embodiment, the amount of Ni is about 1.0 to about 3.0 wt%, more specifically about 1.0 to about 2.0 wt%, even more specifically about 1.0 to about 1.5 wt%. The predetermined maximum amount of retained austenite improves the fracture toughness of the claimed alloys. Ni is M S significantly lowers the temperature, and the amount disclosed in the present application provides M compatible with the heat treatment temperature and time disclosed in the present application S temperature, which provides the desired martensitic microstructure and simultaneously promotes the desired amount of retained austenite. The amount of Ni described herein also increases the Charpy V-notch toughness of the martensitic stainless steel alloys described herein. Ni is added to promote austenite formation during austenitization and minimize the formation of delta ferrite. In the present alloy, an excessive amount of retained austenite is undesirable, as it makes the microstructure susceptible to corrosive attack. The presence of austenite in the microstructure creates a galvanic couple with adjacent martensite, leading to accelerated attack in corrosive aqueous media. Retained or untransformed austenite forms a galvanic couple with adjacent martensite. Therefore, the retained austenite content should be kept at a maximum of less than 2 vol% of the alloy microstructure to ensure the best pitting corrosion resistance.
[0022] As described above, C (carbon) is an essential element and is present in an amount sufficient to provide predetermined hardness and / or predetermined tensile strength. The amount of C also affects coarse M 23The amount of C is selected to avoid the formation of C6 carbides. These carbides preferentially nucleate at grain boundaries, reducing toughness. Chromium carbides also deplete the matrix surrounding the chromium carbides, leading to reduced corrosion resistance. In one embodiment, C is present in an amount of less than about 0.05% by weight. In another embodiment, C is present in an amount of about 0.020 to about 0.040% by weight, more specifically about 0.20 to about 0.030% by weight, and even more specifically about 0.025% by weight. In one embodiment, the predetermined hardness is about 30 to about 42 HRC, and the predetermined ultimate tensile strength (UTS) is about 150 to about 200 ksi. The amount of C can be used in conjunction with low-temperature tempering heat treatment as described herein, as it provides a predetermined strength and fracture toughness sufficient for use in turbine airfoil components (e.g., stator and rotor blades of turbine compressors, more specifically stator and rotor blades of turbine compressors suitable for use in the first to fifth stages of industrial gas turbine compressors).
[0023] Referring to Figure 1, a method 100 for producing a forged martensitic corrosion-resistant stainless steel alloy is disclosed according to another embodiment. Method 100 includes step 110 of preparing a forged preform of a martensitic corrosion-resistant stainless steel alloy containing about 12.0 wt% to about 16.0 wt% chromium, more than 16.0 wt% to about 20.0 wt% cobalt, about 6.0 wt% to about 8.0 wt% molybdenum, about 1.0 wt% to about 3.0 wt% nickel, about 0.020 wt% to about 0.040 wt% carbon, the remainder being iron and unavoidable impurities. The stainless steel alloy can be prepared by any suitable method, including processing substantially conventionally. For example, the alloy may be produced by electric furnace melting in argon oxygen decarburization (AOD) ladle refining and subsequent electroslag remelting (ESR) of the ingot. Other similar melting methods may also be used. Next, a rod can be manufactured using an appropriate forming operation, such as various forging methods, to produce a forged preform having the shape of a desired article, including various articles described herein, such as turbine compressor blade sections.
[0024] Method 100 also includes step 120 of heating the forged preform to a solution treatment temperature for a time sufficient to form a solution-treated microstructure. In one embodiment, the solution treatment temperature is from about 2000°F to about 2100°F, and the solution treatment time is from about 1 hour to about 3 hours.
[0025] The method further includes step 130 of cooling the forged preform and the solution-treated microstructure to room temperature to form a martensitic microstructure. Any suitable cooling method that provides a cooling rate sufficient to promote martensitic transformation of the alloy microstructure may be used. In one embodiment, cooling comprises water, polymer or oil quenching. Gas or air quenching is insufficient to prevent the formation of sigma phase during cooling. More specifically, a cooling rate of 0.25°C / second is required to suppress sigma phase formation in high-alloy stainless steel.
[0026] The method further includes step 140 of immersing the forged preform 140 in a cryogenic liquid at a temperature below -300°F. Cryogenic cooling transforms the residual austenite phase into martensite. Cryogenic treatment is performed with a cryogenic liquid (such as liquid nitrogen or liquid helium) to a temperature below -300°F, and is required to transform residual austenite into martensite after a conventional quenching operation. This cryogenic operation is performed between the quenching / cooling 130 process step and the tempering / heating 150 process step.
[0027] The method also includes a heating step 150 to a tempering temperature of less than approximately 600°F for a predetermined tempering time sufficient to form a tempered forged preform containing a tempered martensite microstructure. Any suitable heating method and tempering time may be used. In one embodiment, the predetermined tempering time is approximately 3 to 6 hours. In one embodiment, the tempered forged preform includes a turbine blade preform or a compressor blade preform. Low tempering temperatures of less than 600°F are used to avoid the formation of precipitates described herein, particularly the brittle chi phase, Laves phase, and sigma phase. It has been found that when more than 3.5% Mo is present in 12%Cr steel, high-temperature aging reactions based on the precipitation of the Laves phase occur. High Mo content may lead to high-temperature formation of intermetallic chi and sigma phases, increasing brittleness and reducing tensile ductility. The formation of these compounds results in a dramatic loss of impact resistance. Therefore, the focus is on solid solution strengthening (from both the substitution element and interstitial carbon aspects) and low-temperature tempering at temperatures below 600°F. Low-temperature tempering establishes a predetermined maximum operating temperature for these alloys, which is lower than the tempering temperature, preferably at least about 50 to about 100°F lower to avoid subsequent martensite tempering and changes in the alloy microstructure. It is desirable to retain as much Cr and Mo as possible in the solid solution to provide corrosion resistance and to prevent these elements from bonding to intermetallic compounds or carbides. The formation of the sigma phase during quenching or tempering is a problem. The formation of the sigma phase is detrimental to corrosion resistance and toughness. The tempering temperature is kept below 600°F to prevent the formation of the sigma, chi, and laves phases, which embrittle the alloy and reduce its pitting resistance.
[0028] In addition to pitting corrosion resistance, the martensitic stainless steel alloys disclosed herein possess a combination of strength, ductility, and fracture toughness, making them suitable for use in forming various turbine airfoils, blades, and other components. In one embodiment, the martensitic stainless steel alloy exhibited superior pitting corrosion resistance compared to GTD-450 and GTD-450+ after 500 hours of salt spraying in accordance with ASTM G85, and in another embodiment, showed virtually no pitting corrosion after 500 hours of salt spraying in accordance with ASTM G85, which can also be described as no pitting corrosion at all with respect to this salt spray experiment in one embodiment. In another embodiment, the martensitic stainless steel alloy disclosed herein showed virtually no pitting corrosion after 1000 hours of salt spraying in accordance with ASTM B117, which can also be described as no pitting corrosion at all with respect to this salt spray experiment in one embodiment. In one embodiment, the martensitic stainless steel alloy has an ultimate tensile strength of about 150 ksi or more, more specifically about 150 to about 200 ksi. In another embodiment, the martensitic stainless steel alloy has a room-temperature elongation of about 11%. In yet another embodiment, the martensitic stainless steel alloy has a tensile reduction in cross-sectional area of about 39%. In yet another embodiment, the martensitic stainless steel alloy has a Charpy V-notch impact toughness of about 20 J (16 ft-lbs).
[0029] The alloys and methods disclosed herein can be used to form turbine airfoil components, including those used in compressor airfoil components for industrial gas turbines. Typical compressor airfoils in the form of turbine compressor blades are well known. Compressor blades have a leading edge, a trailing edge, a tip, and a blade root (such as a dovetail root suitable for removable mounting to the compressor disk). The blade span (wing length) extends from the tip to the blade root. The blade surface contained within the span constitutes the airfoil surface of the turbine airfoil. The airfoil surface is the portion of the turbine compressor airfoil exposed to the airflow path from the turbine inlet through the compressor section of the turbine to the combustion chamber and other parts of the turbine. The alloys and methods disclosed herein are particularly useful for use in turbine compressor airfoils in the form of rotor and stator blades of turbine compressors, but can be broadly applied to all kinds of turbine compressor airfoils used in a wide variety of components. Examples of such components include turbine airfoils related to turbine compressor stator blades and nozzles, shrouds, liners, and other turbine compressor airfoils, i.e., turbine components having airfoil surfaces such as diaphragm components, seal components, valve stems, nozzle boxes, and nozzle plates. While these alloys and methods are useful for the rotor and stator blades of gas turbine compressors, they can also potentially be used for turbine components of industrial steam turbines (e.g., compressor rotor and stator blades, steam turbine buckets, and other steam turbine airfoil components), petroleum and gas machine components, and other applications requiring high tensile strength, fracture toughness, and pitting corrosion resistance, provided that the operating temperature range of the component matches the specified maximum operating temperature of the alloy described herein.
[0030] In this application, the indefinite article does not indicate a limitation of quantity, but rather means that there is one or more items to which the indefinite article is attached. The modifier "about" used with respect to quantity encompasses the stated value and has a contextual meaning (e.g., including the degree of error associated with the measurement of a particular quantity). Furthermore, unless otherwise defined, all scopes disclosed in this application are inclusive and can be combined (for example, a scope described as "about 25% by weight or less, more specifically 5% by weight to about 20% by weight, and more specifically about 10% by weight to about 15% by weight" encompasses the upper and lower limits of those scopes and all intermediate values (e.g., "about 5% by weight to about 25% by weight, about 5% by weight to about 15% by weight," etc.). When "about" is used with respect to a list of alloy composition components, it applies to all listed components, and when used with respect to a range, it applies to the upper and lower limits of that range. Finally, unless otherwise defined, the scopes disclosed in this application Technical and scientific terms have the same meaning as they would be commonly understood by those skilled in the art. Terms with the plural suffix "s" in parentheses indicate that they encompass both the singular and plural forms of the term, including one or more of them (for example, "metal(s)" includes one or more metals). Throughout this specification, phrases such as "one embodiment," "another embodiment," and "embodiment" mean that a particular component (e.g., feature, structure, and / or characteristic) described in relation to that embodiment is included in one or more embodiments described in this application, and may or may not be present in other embodiments.
[0031] The term "including" as used in reference to the alloy compositions described herein is understood to specifically disclose and encompass embodiments in which the alloy composition "substantially consists of" the described components (i.e., includes the described components but does not include other components that substantially adversely affect the disclosed basic and novel features) and embodiments in which the alloy composition "consists of" the described components (i.e., contains only the described components, except for impurities that are naturally and inevitably present in each of the described components).
[0032] Although the present invention has been described in detail with respect to a limited number of embodiments, it should be clear that the present invention is not limited to these disclosed embodiments. The present invention can be modified to introduce numerous changes, modifications, substitutions, or equivalent configurations that are in line with the technical idea and scope of the present invention, even if not described herein. Furthermore, although various embodiments have been described, aspects of the present invention may include only a portion of the embodiments described. Therefore, the present invention is not limited by the foregoing description, but is limited solely by the technical scope described in the claims.
[0033] Other aspects of the present invention are shown in the following embodiments. [Embodiment 1] A method for manufacturing a forged martensitic stainless steel alloy, comprising the steps of: preparing a forging preform of a martensitic pitting-resistant stainless steel alloy containing about 12.0% to about 16.0% by weight of chromium, more than 16.0% to about 20.0% by weight of cobalt, about 6.0% to about 8.0% by weight of molybdenum, about 1.0% to about 3.0% by weight of nickel, about 0.020% to about 0.040% by weight of carbon, the remainder being iron and unavoidable impurities, wherein the alloy has a microstructure containing about 15 volume% or more of retained austenite phase in its microstructure; and forging A method comprising the steps of: heating a preform to a solution temperature for a time sufficient to form a solution microstructure; cooling the forged preform and the solution microstructure to room temperature in a liquid; then immersing the forged preform in a cryogenic liquid to transform the retained austenite phase in the microstructure into martensite; heating the forged preform to a tempering temperature of less than 600°F for a tempering time sufficient to form a tempered forged preform containing a tempered martensite microstructure; and cooling the tempered forged preform to room temperature. [Embodiment 2] The method according to Embodiment 1, wherein the solution temperature includes approximately 2000 to 2100°F and the time includes approximately 1 to 3 hours. [Embodiment 3] The method according to any one of Embodiments 1 to 2, wherein the liquid in the cooling step includes oil or water, and the forged preform and solution-treated microstructure are immersed in the liquid. [Embodiment 4] The method according to any one of Embodiments 1 to 3, wherein the cryogenic liquid in the immersion step includes liquid nitrogen or liquid helium. [Embodiment 5] The method according to any one of Embodiments 1 to 4, wherein the tempering time is approximately 3 hours to approximately 6 hours. [Embodiment 6] The method according to any one of Embodiments 1 to 5, wherein the tempered forging preform includes a turbine blade preform or a compressor blade preform. [Embodiment 7] The method according to any one of Embodiments 1 to 6, wherein the retained austenite phase constitutes 2 volume percent or less of the microstructure. [Embodiment 8] The method according to Embodiment 1, wherein the alloy has a microstructure that is substantially free of the Raves phase, Chi phase, or Delta Ferrite phase. [Embodiment 9] The method according to any one of Embodiments 1 to 8, wherein the alloy has a microstructure that substantially does not contain a sigma phase. [Embodiment 10] A process for providing a forged martensitic corrosion-resistant stainless steel alloy forged preform, comprising: a process for providing a forged preform of a martensitic corrosion-resistant stainless steel alloy containing approximately 12.0% to 16.0% by weight of chromium, over 16.0% to 20.0% by weight of cobalt, approximately 6.0% to 8.0% by weight of molybdenum, approximately 1.0% to 3.0% by weight of nickel, approximately 0.020% to 0.040% by weight of carbon, the remainder being iron and unavoidable impurities, wherein the alloy has a microstructure in which retained austenite phase is contained in less than 2% by volume of the microstructure; and a process for heating the forged preform to a solution temperature for a time sufficient to form a solution microstructure. A method comprising: a step of cooling a forged preform and a solution-treated microstructure to room temperature with a liquid, wherein the liquid is oil, and the forged preform is immersed in the oil; a step of immersing the forged preform in a cryogenic liquid to transform the retained austenite phase in the microstructure into martensite, wherein the cryogenic liquid is liquid nitrogen or liquid helium and is at a temperature of less than -300°F; a step of heating the forged preform to a tempering temperature of less than 600°F for a tempering time sufficient to form a tempered forged preform containing a tempered martensite microstructure; and a step of cooling the tempered forged preform to room temperature. [Embodiment 11] The method according to Embodiment 10, wherein the alloy has a microstructure that substantially does not contain a sigma phase. [Embodiment 12] A forged martensitic stainless steel alloy containing approximately 12.0% to 16.0% by weight of chromium, over 16.0% to approximately 20.0% by weight of cobalt, approximately 6.0% to 8.0% by weight of molybdenum, approximately 1.0% to 3.0% by weight of nickel, approximately 0.020% to 0.040% by weight of carbon, the remainder being iron and unavoidable impurities, and having a microstructure in which retained austenite phase is present in less than 2% by volume of the microstructure. [Embodiment 13] The alloy according to embodiment 12, wherein the alloy has a microstructure that substantially does not contain a sigma phase. [Embodiment 14] The alloy according to Embodiment 12 or Embodiment 13, wherein the alloy has a microstructure that substantially does not contain the Laves phase, the Chi phase, and the Delta Ferrite phase. [Embodiment 15] The alloy according to any one of Embodiments 12 to 14, wherein the alloy includes a turbine blade preform or a compressor blade preform. [Embodiment 16] An alloy comprising approximately 12.0% to 16.0% by weight of chromium, over 16.0% to approximately 20.0% by weight of cobalt, approximately 6.0% to 8.0% by weight of molybdenum, approximately 1.0% to 3.0% by weight of nickel, approximately 0.020% to 0.040% by weight of carbon, the remainder being iron and unavoidable impurities, and having a microstructure substantially free of sigma phases. [Embodiment 17] The alloy according to any one of Embodiments 10 to 16, wherein the alloy has a microstructure in which retained austenite phase is contained in less than 2 volume percent of the microstructure. [Embodiment 18] The alloy according to any one of Embodiments 10 to 17, wherein the alloy has a microstructure that is substantially free of the Laves phase, the Chi phase, and the Delta Ferrite phase. [Embodiment 19] The alloy according to any one of Embodiments 10 to 18, wherein the alloy includes a turbine blade preform or a compressor blade preform.
Claims
1. A method (100) for producing a forged martensitic stainless steel alloy, wherein the method is A step (110) to prepare a forging preform of a martensitic pitting-resistant stainless steel alloy consisting of 12.0% to 16.0% by weight chromium, over 16.0% to 20.0% by weight cobalt, 6.0% to 8.0% by weight molybdenum, 1.0% to 3.0% by weight nickel, 0.020% to 0.040% by weight carbon, the remainder being iron and unavoidable impurities, The process (120) involves heating the forged preform to a solution temperature of 2000°F (1093°C) or higher for at least one hour, which is sufficient time to form a solution microstructure. The process (130) involves cooling the forged preform and solution-treated microstructure to room temperature with a liquid, Next, in order to transform the retained austenite phase in the microstructure into martensite, the forged preform is immersed in an cryogenic liquid at a temperature of less than -300°F (-184°C) (140), The process (150) involves heating the forged preform to a tempering temperature of less than 600°F (315°C) for at least 3 hours, which is a sufficient tempering time to form a tempered forged preform containing a tempered martensite microstructure. The process of cooling the tempered forged preform to room temperature (160) A method comprising the following, wherein the resulting forged martensitic stainless steel alloy has a microstructure containing 2 volume percent or less of retained austenite phase.
2. The method according to claim 1, wherein the solution temperature is 2000 to 2100°F (1093 to 1150°C) and the time is 1 to 3 hours.
3. The method according to claim 1 or 2, wherein the liquid in the cooling step (130) includes oil or water, and the forged preform and solution-treated microstructure are immersed in the liquid.
4. The method according to any one of claims 1 to 3, wherein the cryogenic liquid in the immersion step (140) includes liquid nitrogen or liquid helium.
5. The method according to any one of claims 1 to 4, wherein the tempering time is 3 to 6 hours.
6. The method according to any one of claims 1 to 5, wherein the tempered forging preform includes a turbine blade preform or a compressor blade preform.
7. The method according to any one of claims 1 to 6, wherein the alloy has a microstructure that does not contain a Laves phase, a Chi phase, or a delta-ferrite phase.
8. The method according to any one of claims 1 to 7, wherein the alloy has a microstructure that does not contain a sigma phase.
9. A forged martensitic stainless steel alloy, wherein the alloy is 12.0% to 16.0% by weight of chromium, Cobalt in amounts exceeding 16.0% by weight to 20.0% by weight, 6.0% to 8.0% by weight of molybdenum, 1.0% to 3.0% by weight of nickel, 0.020% to 0.040% by weight of carbon, An alloy consisting of the remainder iron and unavoidable impurities, having a microstructure in which retained austenite phase is present in less than 2 volume percent of the microstructure.
10. The alloy according to claim 9, wherein the alloy has a microstructure that does not contain a sigma phase.
11. The alloy according to claim 9 or claim 10, wherein the alloy has a microstructure that does not contain a Laves phase, a Chi phase, and a delta ferrite phase.
12. The alloy according to any one of claims 9 to 11, wherein the alloy includes a turbine blade preform or a compressor blade preform.
Citation Information
Patent Citations
JP1966013968Y1
Corrosion pitting resistant martensitic stainless steel
JP2016166409A
Ultra-High Strength Stainless Steels
US20090081068A1